Thermophysical Properties of Nanofluids - Arslan, R.; Ozdemir, V. A.; Akyol, E.; Dalkilic, A. S.; Wongwises, S. (BENTHAM SCIENCE PUBL LTD, 2021)
Nanofluids, which consist of base liquid and nano-sized conductive particles, are widely acclaimed as a new generation liquid for heat transfer applications. Since they possess a variety of conductive particles, they can be efficiently utilized in a heat exchanger. These nano-sized conduc-tive particles can increase the surface area, thus the heat transfer area, changing their thermophysical features. Density, thermal conductivity, viscosity, and heat capacity are crucial parameters and can-not be underestimated in heat transfer. These properties can be manipulated by the particle and base-liquid and can significantly influence the performance of nanofluids. In the last decade, several mod-els, equations, and investigations have been performed to examine the parameters that promote these properties. A review is necessary to locate terms for classifying studies that are both compatible and contradictory to the effects of density, thermal conductivity, viscosity, and heat capacity on the per-formance of nanofluids.
Keywords: Review; nanofluids; viscosity; specific heat; thermal conductivity; density; EFFECTIVE THERMAL-CONDUCTIVITY; HEAT-TRANSFER ENHANCEMENT; GLYCOL-BASED NANOFLUIDS; WATER-BASED AL2O3; ETHYLENE-GLYCOL; DYNAMIC VISCOSITY; AQUEOUS SUSPENSIONS; PHYSICAL PROPERTIES; HYBRID NANOFLUID; BROWNIAN-MOTION; Biotechnology & Applied Microbiology; Science & Technology - Other Topics; Materials Science